PERVAINCONSA Scale to Measure the Consumer Behavior of Online Stores of MSMEs Engaged in the Sale of Clothing - García-Salirrosas, Elizabeth Emperatriz (2022)
The objective of the research was to validate an instrument designed to measure the variables value perception, purchase intention, trust, and satisfaction of Micro, Small and Medium Enterprises (MSMEs) dedicated to selling clothing. The PERVAINCONSA Scale (acrostic formed with the initial letters of the Spanish words “Percepción de Valor”, “Intención de Compra”, “Confianza” and “Satisfacción”) was constructed. A total of 238 questionnaires were collected from users of online clothing stores in Peru, Mexico, and Colombia (38.7% men and 61.3% women) with an average age of 24.29 years (SD = 8.04). The KMO and Barlett’s test was 0.958. Confirmatory factor analysis provided an excellent model (χ2 = 372.76, gl = 164; χ2/df = 2.27; CFI = 0.956; RMSEA = 0.073, SRMR = 0.035; and Pclose = 0.00). The model showed good scale reliability given that the composite reliability index (CFI), and all values exceeded the minimum threshold of 0.6. The results suggest that this first version of the PERVAINCONSA presents adequate psychometric evidence to measure value perception, purchase intention, trust and satisfaction in consumers of online stores in Peru, Mexico and Colombia. Thus, it seeks to contribute to the advancement of the scientific study of these important variables in the study of consumer behavior in Latin America.